Exploring EFL teachers’ beliefs and practices of formative assessment in Chinese context - Wanrong Lei; Zhibin Lei (PLoS ONE, 2025)
Formative assessment (FA) has become central to effective EFL pedagogy, promoting feedback, engagement, and self-regulated learning. Yet in the Chinese EFL context, little is known about how university teachers actually conceptualize and enact FA in their classrooms. This study explores EFL teachers’ beliefs, self-reported practices, and challenges in implementing FA through a mixed-methods design that combines a survey (N = 288) with follow-up interviews (n = 11). Results revealed that most teachers hold positive beliefs about FA and acknowledge its potential to enhance student motivation and engagement. However, the frequency of FA practices varies significantly among the participants. Teachers tend to select their FA strategies within institutional limits and rely on technological platforms for implementing these strategies. Despite acknowledging FA’s role in informing teaching improvements and student learning, it was frequently used for grading and managing classroom participation. Challenges included time constraints, large class sizes, inadequate technological support, difficulty in establishing clear assessment criteria, and underutilization of self- and peer assessment. These findings highlight the necessity for multifaceted interventions to better align EFL teachers’ beliefs with their practices in FA.